Corporate Life Cycle, Corporate Governance and Corporate Social Responsibility Disclosure - Rossy Azella Rahmawati; Indri Kartika (Universitas Pendidikan Indonesia, 2023)
This study examines the effect of CLC in the mature phase, size of the board of commissioners, size of the board of directors, and gender diversity on CSR disclosure with company size, profitability, slack, MTB, RnD, and company age as control variables. This study used 352 manufacturing companies listed on the IDX for 2019-2021. Secondary data was obtained from annual reports and analyzed quantitatively through multiple linear regression analysis with SPSS 25. This study found that CLC in the mature phase and the size of the board of directors had a significant positive effect on CSR disclosure. The size of the board of commissioners had an insignificant positive effect, while gender diversity had an insignificant negative effect. Companies in the mature phase with many directors will become increasingly involved in CSR because their conditions are stable. Meanwhile, commissioners focus more on financial performance, and male directors still dominate, so their influence is insignificant. This study implies that companies in the mature phase need to implement CSR to gain the trust of stakeholders so they can be sustainable in the long term, and the government needs to encourage companies to be committed to implementing CSR. Investors do not hesitate to invest in companies in the mature phase that have good social responsibility because these companies can be sustainable in the long term. This study adds a gender diversity variable, uses the latest GRI Standards with 148 indicators, and uses manufacturing companies registered on the IDX for 2019-2021 as the novelty from previous research.